A Semantic Analysis of Phrasal Verbs Produced by Hillary Clinton in The Commencement Speech - Asriyani Medina; Ria Saraswati (JEdu: Journal of English Education, 2021)
The aim of this research is to analyse a semantic analysis of phrasal verbs produced by Hillary Clinton in her commencement speech. The writer focused on the implied meanings and the phrasal verbs used by Hillary Clinton during her speech at Wellesley College in 2017. In this analysis, the writer used a qualitative descriptive method and a library research technique to collect the data. In analysing the implied meanings of phrasal verbs, the writer applied Geoffrey Leech’s theory. According to the result, the writer found that there were 10 or 25% phrasal verbs with conceptual meaning, 4 or 10% phrasal verbs with connotative meaning, 16 or 39% phrasal verbs with affective meaning, 7 or 17% phrasal verbs with social meaning, and 3 or 9% with thematic meaning. Therefore, the most dominant meaning in phrasal verbs produced by Hillary Clinton was affective meaning. Meanwhile, in analysing the phrasal verbs, the writer used the theory from Larsen-Freeman and Celce-Murcia. There were three types of phrasal verbs categorized into literal phrasal verbs, aspectual phrasal verbs, and idiomatic phrasal verbs. It can be concluded that there were 17 or 42% literal phrasal verbs, 10 or 25% aspectual phrasal verbs, and 13 or 33% idiomatic phrasal verbs. Thus, the most frequent type of phrasal verbs used during the speech were literal phrasal verbs.